How Are We Doing?: In Conversation With Amélie Perron, on Nursing as "Disobedient Practice: Care of the Nurse's Self, Parrhesia, and the Dismantling of a Baseless Paradox" - Hopkins-Walsh, Jane (Nursing philosophy, 2025)
This article is a dialogue between authors, revisiting Perron's 2013 Nursing Philosophy paper "Nursing as disobedient practice: Care of the nurse's self, parrhesia, and the dismantling of a baseless paradox'. Perron's paper argues for the ethical imperative of nursing as political action - including philosophical explorations of disobedience, care of the self, freedom, agency, and "parrhesia": the act of speaking boldly and fearlessly against dominant views of apolitical niceness in nursing. The conversation roots in the present time-space of declining rights and rising authoritarianism in the United States, Canada, and elsewhere, with risks of harm to nurses and the diverse people and communities that nurses accompany in practices of care, policy, research, and education. Topics discussed include: the historical contexts that sparked Perron's paper, post-pandemic lessons and implications for nursing, the relationship of nursing organizations to power, ongoing challenges of empowering nurses to become more politically minded and active, and advancing political thought as a morally necessary form of evidence to inform all nursing domains. The conversation concludes with hopes for a collective imagination in nursing grounded in community connections, creative pedagogy, and a bold embrace of theoretical works that inspire and guide nursing actions for justice and equity.